STUDI LITERATUR: PENGARUH PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR MATEMATIKA DI SEKOLAH DASAR - Muthmainah, Aisyah; Suntari, Yustia; Yudha, Chrisnaji Banindra (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
Mathematics learning in elementary schools requires the application of appropriate learning models so that student learning outcomes can be optimal. This article is compiled using a literature study method that analyzes various research results related to the influence of Jigsaw-type cooperative learning on mathematics learning outcomes in elementary schools. The Jigsaw-type cooperative learning model places students in small heterogeneous groups, where each member is responsible for studying and delivering certain parts of the material to their original group. Based on the analysis of various studies, it was found that the application of the Jigsaw model was consistently able to improve students' mathematics learning outcomes at various grade levels. This increase is reflected in the increase in average grades, percentage of learning completion, and student absorption in each learning cycle. The results of statistical tests in several studies also showed that the influence of the Jigsaw model on learning outcomes was scientifically significant. Thus, this study confirms that Jigsaw-type cooperative learning is effectively implemented as a strategy to improve mathematics learning outcomes in elementary schools. These findings are expected to be a reference for teachers and educational policymakers in choosing an innovative and results-oriented learning approach.